Small-Scale Analysis of the Local Multiplier Effect in the Development of Ghanjaran Park: Impacts on MSMEs and Local Labor Absorption - Deandra Suryanto Putri; Adinda Zahrah Putri Purnama; Irma Puspita Sari; Noor Eka Wahyu Ningrum; Faiza Wardati; Zahfira Destine Alfina Amayosi; Asnimawati Asnimawati (CV. Ulil Albab Corp, 2026)
The development of tourism villages serves as a strategy to enhance local economic growth by increasing activity among micro, small, and medium enterprises (MSMEs) and facilitating local labor absorption. Ghanjaran Park, as a village-based tourist destination, provides a relevant context for examining local economic dynamics. This study investigates the local multiplier effect and the factors influencing it in relation to MSME development and local labor absorption. A quantitative approach is employed, utilizing descriptive-analytical methods to assess the local multiplier effect at a small scale. The analysis draws on income and expenditure data from MSME participants. Findings indicate an LM3 value of 2.57, which demonstrates robust local economic turnover during the initial two cycles. In subsequent cycles, economic leakage is observed, attributed to limited capital, insufficient local raw materials, and dispersed business locations. The effect on labor absorption remains constrained, as increased MSME income has not led to a substantial increase in employment. Strengthening local economic linkages is necessary to optimize the multiplier effect and ensure more equitable and sustainable benefits.